A dynamic multi-objective green supply chain network design for perishable products in uncertain environments, the coffee industry case study. Issue 3 (3rd July 2022) - Torabzadeh, Seyed Ahmad; Nejati, Erfan; Aghsami, Amir; Rabbani, Masoud
ABSTRACT: One of the most critical issues for any production organization to compete in the current competitive business environment is supply chain network design (SCND). Besides, by increasing greenhouse gas emissions, various organizations have imposed many restrictions to prevent the overproduction of these gases in their production planning. This study develops a mathematical model for the location-allocation-inventory problem based on a real case study to design a three-echelon coffee supply chain network. The primary purpose of the problem is to minimize supply chain costs. Minimizing the CO2 emission was also considered to address the increasing eco-friendly challenges. The problem includes various strategic and tactical decisions, such as the number and capacity of manufacturing centers (MCs) and distribution centers (DCs) to be established, how to allocate factories to distribution centers and DCs to customers, material flow throughout the system, and the number of products stored in warehouses. It should be noted the problem's parameters are considered fuzzy to get closer to reality. Finally, by performing several sensitivity analyses, valuable managerial insights were obtained. Applying the developed model to the case study of a coffee company assisted managers in making optimal strategic decisions to establish new MCs and DCs, and reduce CO2 emissions.